Implementasi Metode Scrum Dan Midtrans Sebagai Payment Gateway Pada Aplikasi Capture Berbasis Mobile - Prasetya, Vithalia Rizki; Darusallam, Ucuk; Mardiani, Eri (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
As technology develops, photography service providers are starting to move from the offline to online phase. However, the previous application was considered less than optimal in meeting user needs. The Agile Scrum method is believed to be the most appropriate for designing and building photography service applications. Because it is suitable and practical, system development using the agile method is designed and implemented. Capture is a mobile application and website that was designed because it was not available in previous research. A new feature for service providers can upload photos and cinematic videos to attract users' attention. For this reason, a mobile-based photography service system was designed using agile development methodology and testing for users and service providers.